2000
DOI: 10.1103/physrevd.62.107502
|View full text |Cite
|
Sign up to set email alerts
|

Higher dimensional radiation collapse and cosmic censorship

Abstract: We study the occurrence of naked singularities in the spherically symmetric collapse of radiation shells in a higher dimensional spacetime. The necessary conditions for the formation of a naked singularity or a black hole are obtained. The naked singularities are found to be strong in the Tipler's sense and thus violating cosmic censorship conjecture.PACS numbers: 04.20.DwThe cosmic censorship conjecture (CCC) put forward some three decades ago by Penrose [1] says that in generic situation all singularities ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
5
19
0
Order By: Relevance
“…Along this null geodesic, the Kretschmann invariant diverges for r → 0 as 22) and hence it is concluded that an ingoing-null naked singularity is formed at v = r = 0. This result is consistent with the results in [25,26].…”
Section: Naked Singularity Formationsupporting
confidence: 93%
“…Along this null geodesic, the Kretschmann invariant diverges for r → 0 as 22) and hence it is concluded that an ingoing-null naked singularity is formed at v = r = 0. This result is consistent with the results in [25,26].…”
Section: Naked Singularity Formationsupporting
confidence: 93%
“…Null dust collapse was studied in the articles, 20,30,42 whose main purpose was to study the cosmic censorship conjecture. They find not only black hole formation, but also naked singularities as the final outcome of collapse, in those settings.…”
Section: Other Interiorsmentioning
confidence: 99%
“…where M 0 = (1/12)κ 2 ρ i a 3 i r 3 and S 0 = (−1/48)κ 4 σ 2 0 r 3 , clearly exhibiting a Schwarzschild-anti-de Sitter metric in retarded null coordinates [163][164][165] with a constant mass M 0 = M 0 + S 0 with corrections due to spin contributions.…”
Section: Exterior Solutionmentioning
confidence: 99%